Kedudukan Hukum Alat Bukti dalam Tindak Pidana Pelecehan Seksual di Peradilan Pidana Indonesia - Kevin Mandala; Erdianto Erdianto; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Evidence occupies an important position. The judge in making a decision will need a lot of time tostudy and analyze in depth the existing evidence and the results of the evidence will be used as aguide in making a decision. Indonesia adheres to a system of proof according to negative law orNegative Wettelijk Stelsel, this can be seen in the provisions of Article 183 of the CriminalProcedure Code, where to convict the Defendant, the Judge must have at least two valid pieces ofevidence plus valid evidence. the judge's conviction, meaning that at least two valid pieces ofevidence, the judge obtains confidence that the crime actually occurred and the defendant was theperpetrator. Therefore, the judge must carefully, thoroughly, and maturely assess and consider thevalue of an evidence by examining the extent to which the "Power of Evidence" or minimumbewijskracht of each piece of evidence as referred to in Article 184 of the Criminal ProcedureCode and besides that the judge must also distinguish between criminal acts other with evidence ofa crime of sexual violence.The objectives to be achieved in this research are the first, namely to find out how the legalposition of evidence in the crime of sexual harassment in the Indonesian criminal court. Second, tofind out the ideal form of regulation regarding the position of evidentiary law in the crime ofsexual harassment in criminal justice in Indonesia.The author conducts research using normative juridical methods or literature studies to obtainsecondary data which is divided into 3 (three) namely primary, secondary and tertiary legalmaterials. In this study, researchers used a statutory approach to study law, namely the principleof justice associated with the problems studied.From the research results, there are three main things that can be concluded: First, regarding thelegal position of evidence in the crime of sexual harassment in the Indonesian criminal justicesystem, it plays an important role. what the defendant has done. Two ideal forms of arrangementregarding the legal position of proof in the crime of sexual harassment in the Criminal Courts inIndonesia are if it is not accompanied by a crime and other evidence that does not meet thestandards in Article 184 of the Criminal Procedure Code. Code, then the proof is useless.Indonesia still adheres to negative evidence by requiring that two pieces of evidence must bepresented in court, and this is difficult to prove in crimes of sexual violence. Therefore, the authoris of the opinion that especially with the crime of sexual violence there is no need to pay attentionto two pieces of evidence, the witness-victim testimony is the key and the perpetrator's lie detectortool is one of the expert statements.Keywords: Legal Standing, Evidence, Sexual Harassment, Criminal Justice